RISK OF CHRONIC GLOMERULONEPHRITIS IN CHILDREN - Arzibekova Umida Abdukadirovna (Galaxy International Interdisciplinary Research Journal, 2024)
A retrospective analysis of risk factors for chronic glomerulonephritis in 210 children was carried out. The role of a combination of several risk factors in the chronic course of the disease has been established. We identified 5 combinations of common risk factors that determine the chronic course of various clinical forms of glomerulonephritis in children. A table has been developed to predict the risk of chronic glomerulonephritis in children.